Chips from a German workshop - Müller, F. Max (Collected works of the Right Hon. F. Max Müller, 1898)
v.1 Recent essays and addresses -- v.2. Biographical essays -- v.3. Essays on language and literature -- v.4. Essays on mythology and folk-lore.